ANALISIS FAKTOR YANG MEMPENGARUHI PERPINDAHAN KAP DI INDONESIA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2010-2012) - Walmi Sholihat; Raja Adri Satriawan; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Auditor switching is a change of public accountant who performedby a company.Auditor changes can occur due to government regulations (mandatory)and wishes the company itself (voluntary ).This study aims to determine the factors thataffecting companies in Indonesia do auditor changes. Variables used in this study is the size of public accountant, turnover management, audit opinion, and share growth. The data used in this study is the financial statement of manufacturing company listed on the Indonesia Stock Exchange (BEI) in 2010-2012. Methods of data collection usingpurposivejudgment sampling. Total sample is as much as 25 companies. The results showed that the variables that significantly affectauditor changes is aturnover management. While other variables such as the size of public accountant, audit opinion, and share growth significantly influence the auditor changes.Keywords: auditor changes, turnover management